2011
DOI: 10.1111/j.1365-2729.2010.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of text messaging on 9‐ and 10‐year‐old children's reading, spelling and phonological processing skills

Abstract: This paper reports on an intervention study that considered the impact of text messaging on 9-to 10-year-old children's literacy skills. One hundred and fourteen children who had never owned a mobile phone before were recruited and randomly allocated to either the intervention or control conditions. All children were pre-and post-tested on a range of reading, spelling and phonological awareness measures. Children in the intervention group were given access to a mobile phone (enabled for text messaging only) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 6 publications
1
48
0
4
Order By: Relevance
“…While exposure to textisms does not have positive impact on children similar to the positive benefits found for adults, such exposure does not have negative impact on spelling ability. Textism usage has also been shown to be positively linked with standard measures of literacy in studies done in the past decade (Wood et al, 2011;Plester et al, 2009;Coe and Oakhill, 2011;Kemp and Bushnell 2011;Kemp, 2010). Plester et al (2009).…”
Section: Crpmentioning
confidence: 99%
See 2 more Smart Citations
“…While exposure to textisms does not have positive impact on children similar to the positive benefits found for adults, such exposure does not have negative impact on spelling ability. Textism usage has also been shown to be positively linked with standard measures of literacy in studies done in the past decade (Wood et al, 2011;Plester et al, 2009;Coe and Oakhill, 2011;Kemp and Bushnell 2011;Kemp, 2010). Plester et al (2009).…”
Section: Crpmentioning
confidence: 99%
“…It would also be beneficial to examine the effects of long term exposure to textisms, as this research only presents a snapshot of the effects of textism exposure on spelling. Although a ten-week study found that textism usage was significantly positively related to spelling test scores (Wood et al, 2011), studies concerning long term effects of textism usage have yet to be published.…”
Section: Crpmentioning
confidence: 99%
See 1 more Smart Citation
“…En eff et, on retrouve autant des enquêtes concluant que la CEMO a une infl uence négative sur la compétence orthographique des jeunes (Zahid et Mehmood, 2013 ;Tayebinik et Puteh, 2012 ;Dansieh, 2011 ;Rosen et al , 2010), que des études y voyant au contraire un impact positif (Bernicot et al , 2014 ;Wood et al , 2011b ;Wood et al , 2011a ;Plester et al , 2008 ;Bouillaud et al , 2007), et d'autres enfi n qui n'observent aucune corrélation entre ces deux variables (Aziz et al , 2013 ;Kemp et Bushnell, 2011 ;Asmaak Shafi e et al , 2010 ;Drouin et Davis, 2009 ;Spooren, 2009 ;Volckaert-Legrier et al , 2009). …”
unclassified
“…Wood et al (2011a) . Bien que la diff érence entre les performances aux tests langagiers des enfants ayant reçu un téléphone portable pour l'enquête et celles du groupe contrôle n'était pas signifi cative, Wood et al (2011a) ont observé une corrélation positive entre la densité de textismes et les compétences en lecture et en écriture des participants à la fi n des 10 semaines de l'enquête.…”
unclassified